2018
DOI: 10.1186/s12879-018-3467-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of virulence genes and their association with antimicrobial resistance among uropathogenic Escherichia coli isolates from Iranian patients

Abstract: BackgroundUrinary tract infections (UTIs) are one of the most frequent diseases encountered by humans worldwide. The presence of multidrug-resistant (MDR) uropathogenic Escherichia coli (UPEC) harboring several virulence factors, is a major risk factor for inpatients. We sought to investigate the rate of antibiotic resistance and virulence-associated genes among the UPECs isolated from an Iranian symptomatic population.MethodsA total of 126 isolates from inpatients with UTI from different wards were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
36
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 39 publications
15
36
1
2
Order By: Relevance
“…The sfa was the second most predominant adhesin gene (81%) in our isolates that was in agreement with a research carried out in Shiraz (Fars province, Iran) with a frequency of 79.4% (29). In previous reports, the prevalence of the sfa was conversely less than 30% (7).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The sfa was the second most predominant adhesin gene (81%) in our isolates that was in agreement with a research carried out in Shiraz (Fars province, Iran) with a frequency of 79.4% (29). In previous reports, the prevalence of the sfa was conversely less than 30% (7).…”
Section: Discussionsupporting
confidence: 93%
“…In previous reports, the prevalence of the sfa was conversely less than 30% (7). Nevertheless, the exact role of S-fimbriae is not clarified; therefore, the distribution of bacterium within the host tissue depends on this adhesin marker (29). In our isolates, the papC was the third most prevalent adhesin gene (57%) that was similar to a study conducted in Jahrom (Fars province, Iran) (30).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Se concluyó que la concentración óptima de cebadores es 0,1 μM con 0,5 UI de concentración de Taq. Porcentaje cina estaban asociadas significativamente, lo que difiere con lo reportado por Malekzadegan, et al (19) , quienes no encontraron asociación entre el gen afa y la no sensibilidad a la amikacina, pero sí entre la presencia del gen afa y la producción de BLEE.…”
Section: Discussionunclassified
“…To date, more than 350-different ESBL have been described and mainly are encoded in plasmids. [26][27][28] Some investigations indicated that depending on enzyme substrate, the strains can be classified as ESBL producers or carbapenemases producers. 29,30 This is important because carbapenems are in the list of last resource antibiotics for treatment.…”
Section: Introductionmentioning
confidence: 99%